2013
DOI: 10.1017/s0031182013001625
|View full text |Cite
|
Sign up to set email alerts
|

The impact of co-infections on the haematological profile of East African Short-horn Zebu calves

Abstract: SUMMARYThe cumulative effect of co-infections between pathogen pairs on the haematological response of East African Short-horn Zebu calves is described. Using a longitudinal study design a stratified clustered random sample of newborn calves were recruited into the Infectious Diseases of East African Livestock (IDEAL) study and monitored at 5-weekly intervals until 51 weeks of age. At each visit samples were collected and analysed to determine the infection status of each calf as well as their haematological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…The mean TWBC, neutrophil and lymphocyte counts for T. vivax infected WASH cattle in this study were higher than those for the uninfected. Similar observations of leukocytosis due to trypanosome infection have been made in rabbits ( Emeribe & Anosa, 1991), vervet monkeys ( Kagira et al , 2006) and Zebu cattle ( Berthier et al , 2015; Van Wyk et al , 2014). Ilemobade et al (1982) suggested that trypanosome-induced severe leukopenia could compromise the protective immunity of cattle to other diseases.…”
Section: Discussionsupporting
confidence: 77%
“…The mean TWBC, neutrophil and lymphocyte counts for T. vivax infected WASH cattle in this study were higher than those for the uninfected. Similar observations of leukocytosis due to trypanosome infection have been made in rabbits ( Emeribe & Anosa, 1991), vervet monkeys ( Kagira et al , 2006) and Zebu cattle ( Berthier et al , 2015; Van Wyk et al , 2014). Ilemobade et al (1982) suggested that trypanosome-induced severe leukopenia could compromise the protective immunity of cattle to other diseases.…”
Section: Discussionsupporting
confidence: 77%
“…Since parasites can bring about distinct changes to host hematology, body condition and immune investment (Budischak et al., 2012, van Wyk et al., 2014), it follows that even disparate parasites can boost (Monteiro et al., 2007b, Knowles, 2011, Thumbi et al., 2014) or suppress one another (Moreno et al., 2013) via their influences on host immune function (Cox, 2001, Ulrich and Schmid-Hempel, 2012). Although the logistics and economics of collecting long-term, individual-based infection data are challenging, these data are critical to study the effects of age, social structure, life history, time, seasonal variation, and co-infection on disease dynamics (Clutton-Brock and Sheldon, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(Silatsa, Simo, et al, 2019b). It is, however, possible that other Rhipicephalus and Hyalomma species that are present in Cameroon for which the ability to transmit T. parva infection has been demonstrated experimentally could potentially evolve to become vectors in future (Norval et al, 1992;Theiler, 1909;Uilenberg, 1981 (Silatsa, Simo, et al, 2019b), the infected animals do not currently pose any risk of infection to naive cattle, although this situation could change in future, since certain AEZs, such as the Adamawa plateau, the western highlands and the coastal belt are climatically suitable for establishment of the major vector R. appendiculatus (Walker et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Other confirmed vectors are R. zambeziensis in parts of Southern Africa and R. duttoni in Angola. Additionally, other Rhipicephalus and Hyalomma species have been shown experimentally to be potential vectors of T. parva group parasites (Norval et al, 1992;Theiler, 1909;Uilenberg, 1981).…”
Section: Introductionmentioning
confidence: 99%